KAMPUNG SABBETA’: DESA WISATA PENGELOLA ULAT SUTRA TERINTEGRASI DAN RAMAH LINGKUNGAN - Yunianti, A. D.; Nuraeni, S.; Malina, A. C.; Suhasman, Suhasman (Buletin Udayana Mengabdi; Vol 20 No 1 (2021): Buletin Udayana MengabdiDO - 10.24843/BUM.2021.v20.i01.p03, 2021)
Kampung Sabbeta' in Pising Village, Donri-donri District, Soppeng Regency, South Sulawesi is a silk development center that has several groups of silk craftsmen who actively produce silk threads. Even so, the productivity of community groups is very low. Their silk threads are still low in quality. Weaving skills are also very limited. In addition, the use of waste, especially mulberry leaves, has not been handled properly. The activities we carry out include the transfer of science and technology to increase community productivity, marketing strategies to improve product competitiveness, and ways of utilizing waste. The results of the transfer of knowledge and technology through FGDs, training, and practice in the field were greeted with high appreciation by the local community. Knowledge related to marketing, silk yarn spinning, eco-print and mushroom cultivation using mulberry leaf waste media has been provided. Especially for the development of eco-print on silk fabrics, they have been successful, their products have various kinds, and have even become one of the souvenirs from Sabbeta Village